Fluorescent Proteins as Biomarkers and Biosensors: Throwing Color Lights on Molecular and Cellular Processes - Stepanenko, Olesya V.; Verkhusha, Vladislav V.; Kuznetsova, Irina M.; Uversky, Vladimir N.; Turoverov, K. K. (Current Protein and Peptide Science, 2008)
Green fluorescent protein (GFP) from jellyfish Aequorea victoria is the most extensively studied and widely used in cell biology protein. GFP-like proteins constitute a fast growing family as several naturally occurring GFP-like proteins have been discovered and enhanced mutants of Aequorea GFP have been created. These mutants differ from wild-type GFP by conformational stability, quantum yield, spectroscopic properties (positions of absorption and fluorescence spectra) and by photochemical properties. GFP-like proteins are very diverse, as they can be not only green, but also blue, orange-red, far-red, cyan, and yellow. They also can have dual-color fluorescence (e.g., green and red) or be nonfluorescent. Some of them possess kindling property, some are photoactivatable, and some are photoswitchable. This review is an attempt to characterize the main color groups of GFP-like proteins, describe their structure and mechanisms of chromophore formation, systemize data on their conformational stability and summarize the main trends of their utilization as markers and biosensors in cell and molecular biology.
Keywords: chromoproteins